Biofuels and the future of food: Competition and complementarities - Tokgoz, Simla; Zhang, Wei; Msangi, Siwa; Bhandary, Prapti (MDPI, 2012)
In this paper, we draw the key linkages between future biofuels growth on agricultural commodity prices, and highlight some of the key uncertainties over OECD fuel and energy policies, and their implications for global agricultural markets and the world food situation. Our results show some of the implications that biofuels expansion has on crop area expansion in regions where environmental concerns exist over land use change and the possible impacts on the environment. We also point to some promising areas for future research and specify some implications for policy interventions.